3 Dimensional Aerodynamic Analysis of Additional Slat and Slot on Airfoil Naca 23018 Using Computational Fluid Dynamic Method - Rimadhani Hermawati, Tarysa; Hariyadi Suranto, Setyo; Pambudiyatno, Nyaris (Nusantara Publisher, 2025)
Slat and Slot is one of the components of high lift devices in addition to the flaps used on the wings of the aircraft. It has a function to provide a lifting force when the attack angle of the aircraft wing is high. The topic studied in this study was the flow that crossed the NACA 23018 airfoil with the addition of slats and slots. The research method used is a 3-dimensional analysis method using ansys fluent software. The test object to be used is the NACA 23018 airfoil. This research was conducted numerically using the CFD (computational fluid dynamic) method. The purpose of this study was to compare the characteristics of fluid flow with or without the addition of slats and slots. The speed used is 40m/s with a spacing of 5%, 8%, and 10% chords and the angle of attack used as variation parameters are (α) = 0°, 2°, 4°, 6°, 8°, 10°, 12°, 15°, 16°, 17°, 18°, 19° and 20°. The results showed that with the addition of slats and slots on the NACA 23018 Airfoil, it can increase the lifting force at the high angle of attack, as well as delay the stall due to delays in airflow separation. In the airfoil variation with a slat clearence of S = 10% (α = 20⁰) has a lift coefficient with the most maximum value and a more even distribution. So in this study, it came to the conclusion that the most effective variation used in the NACA 23018 Airfoil was with a 10% slat clearence at subsonic speed